Multicentre observational status-epilepticus registry: protocol for ICTAL. Issue 2 (15th February 2022) - Jacq, Gwenaelle; Chelly, Jonathan; Quenot, Jean-Pierre; Soulier, Pauline; Lesieur, Olivier; Beuret, Pascal; Holleville, Mathilde; Bruel, Cedric; Bailly, Pierre; Sauneuf, Bertrand; Sejourne, Caroline; Rigaud, Jean Philippe; et al.
Abstract : Introduction: Status epilepticus (SE) is a common life-threatening neurological emergency that can cause long-term impairments. Overall outcomes remain poor. Major efforts are required to clarify the epidemiology of SE and the determinants of outcomes, thereby identifying targets for improved management. Methods and analysis: ICTAL Registry is a multicentre open cohort of critically ill patients with convulsive, non-convulsive or psychogenic non-epileptic SE. Observational methods are applied to collect uniform data. The goal of the ICTAL Registry is to collect high-quality information on a large number of patients, thereby allowing elucidation of the pathophysiological mechanisms involved in mortality and morbidity. The registry structure is modular, with a large core data set and the opportunity for research teams to create satellite data sets for observational or interventional studies (eg, cohort multiple randomised controlled trials, cross-sectional studies and short-term and long-term longitudinal outcome studies). The availability of core data will hasten patient recruitment to studies, while also decreasing costs. Importantly, the vast amount of data from a large number of patients will allow valid subgroup analyses, which are expected to identify patient populations requiring specific treatment strategies. The results of the studies will have a broad spectrum of application, particularly given the multidisciplinary approach used by the IctalGroup research network. Ethics and dissemination: The ICTAL Registry protocol was approved by the ethics committee of the French Intensive Care Society (#CE_SRLF 19-68 and 19-68a). Patients or their relatives/proxies received written information to the use of the retrospectively collected and pseudonymised data, in compliance with French law. Prospectively included patients receive written consent form as soon as they recover decision-making competency; if they refuse consent, they are excluded from the registry. Data from the registry will be disseminated via conference presentations and peer-reviewed publications. Trial registration number: NCT03457831 .